Respuesta :
[tex]\huge\text{Hey there!}[/tex]
[tex]\huge\text{x + x(x + y) + y}[/tex]
[tex]\huge\text{= 4 + 4(4 + 1) + 1}[/tex]
[tex]\huge\text{= 4 + 4(5) + 1}[/tex]
[tex]\huge\text{= 4 + 20 + 1}[/tex]
[tex]\huge\text{= 24 + 1}[/tex]
[tex]\huge\text{= 25}[/tex]
[tex]\huge\boxed{\textsf{Therefore, your answer is: 25}}\huge\checkmark[/tex]
[tex]\huge\text{Good luck on your assignment \& enjoy your day!}[/tex]
~[tex]\huge\boxed{\frak{Amphitrite1040:)}}[/tex]
Hi,
we need to substitute 4 and 1 in the equation, so for every y, we replace it with a 1 and every X with 4 as X= 4, Y = 1
equation: X + X (X + Y) + Y
equation after substituting the numbers: 1 + 1 (1 + 4) + 1
Bidmas rules apply.
expand the bracket first. 1 (1 + 4)=
1 X 1= 1
1 X 4= 4
1 + 4 = 5
then the equation becomes: 1 + 5 + 1= 7
your answer is 7 if you want to evaluate it.
your answer is 1 + 1 (1 + 4) + 1 if you need the equation.
, hope that helps :)